Histopathological and immunohistochemical assessment of the using platelets rich fibrin to reinforce ventral hernioplasty in the sheep model - Ibraheem A. zedan; Llayth M. Alkattan; Saevan S. Al-Mahmood (Iraqi journal of veterinary sciences, 2023)
The guidelines for this experiment were designed to assess the histopathological and immunohistochemical parameters after the topical application of plasma-rich fibrin during hernioplasty in sheep. Twenty-four rams enrolled into two groups, 12 of each. In the control group, hernioplasty was done with polypropylene mesh and a modified sub-lay technique; in the treatment group done the same as the control and reinforced with plasma-rich fibrin (PRF). Tissue samples were collected for histopathological and immunohistochemical investigations. The clinical investigation results indicated developing seroma at the lower region of the surgical site that continued 25 days post-surgery in the control group as a comparison of group PRF which indicated mild seroma. The histopathological examination at 30 days in the control group indicated the presence of focal infiltration of mononuclear inflammatory cells around the mesh and hyperplasia of fibrocytes, deposition of collagen with edema as compared with the treatment group at 15th days post-surgery; there was a high number of new blood vessels, deposition of collagen fibers. Immunohistochemistry indicated a strong positive reaction at seven days post-surgery in control, and the PRF group with IL-6 appeared as golden-brown granules in the cytoplasm of cells around the surgical mesh. At seven days post-surgery, the reaction of VEGF antibody IHC indicated negative and strong positive reactions with VEGF appearing as golden-brown granules in the cytoplasm of cells in the treatment group. In conclusion, using PRF to repair the hernia reduces the incidence of inflammation, and histopathological and immunohistochemistry investigations emphasize an improvement in the healing process of hernia.